Integrating Artificial Intelligence into Service Innovation, Business Development, and Legal Compliance: Insights from the Hainan Free Trade Port Era - Yincheng Li; Shumin Wang; Muhammad Bilawal Khaskheli (Systems)
This research aims to inspect the application of Artificial Intelligence (AI) in product and service innovation from the perspective of the Hainan Free Trade Port (HFTP) and its relationship with corporate transformation, legal compliance, and regulatory oversight. Being critical to the fourth industrial revolution, digital business and international cooperation, technology propels enterprises across various industries to transition from traditional models to intelligent and service-oriented ones. It also elucidates the theoretical foundations of AI products, the digital economy, and service innovation. It can be used to analyzes the challenges enterprises face in the HFTP while implementing AI technology, including funding, technology, management, operations, corporate culture, and innovative concepts. Based on the proposed research methodology, three hypotheses can be formulated. Hypothesis 1 states that the HFTP could facilitate enterprise transformation by applying supportive policies. Hypothesis 2 state that domestic laws and international agreements are urgently needed due to the legal risks arising from artificial intelligence. Hypothesis 3 state that HFTP enterprises comply with these laws while systemically assuring, in theory, and practice, the legal risks of artificial intelligence and its implications for legal regulation, which is a significant aspect of research, addressing legal risks related to data privacy, security, and algorithmic bias with many strategies being proposed. This shows how AI technology can change businesses in the HFTP, demonstrating the application of AI technology in the transformation of enterprises in the HFTP and the various risks they may encounter, providing valuable references for other enterprises regarding the practical significance of AI product and service innovation in the HFTP, and emphasizing the importance of international cooperation and legal instruction.